Optimizing one-pot gold-decorated graphene nanocomposites for fiber optics LSPR sensing - Abu Kasim, Nurul Farhana; Abdul Halim, Norhana; Khim, Ong Keat; Zainal Abidin, Nadiah Husseini; Mahdi, Mohd Adzir; Mohd Yusoff, Norita; Mohd Azmi, Ahmad Farid; Ngah Demon, Siti Zulaikha (Wiley-VCH Verlag, 2026)
Advancements in graphene processing have intensified interest in developing efficient plasmonic sensors that exploit the localized surface plasmon resonance (LSPR) phenomena in metallic nanostructures. A streamlined one-pot synthesis was employed to produce gold nanoparticle-decorated reduced graphene oxide (RGO/AuNP), eliminating complex multi-step procedures to achieve an optimized LSPR signal in a tapered multimode fiber optic (TMMF) sensor. Ascorbic acid (AA) of 50 mg, 150 mg, and 250 mg were chosen to avoid further material waste during fabrication. UV-Vis analysis was shown to determine AuNP spherical size, particle distribution and optical bandgap energy, Eg. Increasing mass of AA resulted in smaller average spherical AuNP and was later confirmed by TEM images of RGO/AuNP. The composite reduced with 50 mg AA, which consisted of ~52 nm AuNP size and the lowest Eg of 3.36 eV was found to be the most suitable plasmonic coating to be applied on the TMMF sensor because of a stronger plasmonic field and efficient electron transfer. The feasibility of the RGO/AuNP coating was further evaluated based on the quality of LSPR response, optical constants and optical bandgap characteristics. Compared to the layer-by-layer composite coating, the one-pot RGO/AuNP deposited fiber yielded stronger absorbance and narrower FWHM demonstrating its promising potential in fiber optic-based sensors.